Online sexual activities among university students: relationship with sexual satisfaction - Gutiérrez-Puertas, Lorena; Márquez Hernández, Verónica; Gutiérrez-Puertas, Vanesa; Granados-Gámez, Genoveva; Rodríguez-García, Mª Carmen; Aguilera-Manrique, Gabriel (Anales de Psicología / Annals of Psychology, 2020)
This study explores online sexual activities and analyzes the relationship between these activities and sexual satisfaction. A total of 236 university students completed self-reported scales. The results indicated that the most frequent online sexual activities were: searching for sexual issues, flirting via chat rooms and viewing erotic or pornographic videos. With regards to the relationship between online sexual activities and sexual satisfaction, it was found that participants who reported not seeking sexual information as well as not using chatrooms for sexual conversations, obtained a higher score in sexual satisfaction. In conclusion, although engaging in activities online for sexual purposes has a high prevalence, its influence on obtaining greater sexual satisfaction is not sufficiently proven.